Intravenous immunoglobulins for the treatment of prolonged COVID-19 in immunocompromised patients: a brief report - Billi, Bénédicte; Cholley, Paul; Grobost, Vincent; Clément, Mélissa; Rieu, Virginie; Le Guenno, Guillaume; Lobbes, Hervé (Frontiers in Immunology, 2024)
Primary humoral deficiency and secondary B-cell depletion may lead to prolonged Sars-Cov-2 infection due to a decreased viral clearance. Prolonged infection is mainly driven by the lack of anti-Sars-Cov-2 immunoglobulin (IVIg) especially in patients with no vaccine response. Anti-spike immunoglobulin can be provided by infusion of convalescent patients' plasma: recent studies highlighted that commercial immunoglobulin show high titers of neutralizing IgG. We conducted a single center retrospective cohort. We included 9 patients (6 males, median age 74 years old): one patient with X-linked agammaglobulinemia and 8 patients treated with rituximab (2 granulomatosis with polyangiitis, 1 neuromyelitis optica, 4 low grade B-cell lymphoma and 1 EBV post-transplant lymphoproliferative disorder). Mean serum globulin was 4 ± 1.6 g/L. 7/8 had received at least 3 doses of mRNA anti-Sars-Cov-2 vaccine (median 4) with no response (anti-Spike IgG 0 for 6 patients). In this specific population requiring oxygen therapy but no intensive care support, the administration of IVIg was well tolerated and provided a swift improvement of clinical status, a significant decrease of inflammation associated to the an improvement of radiological patterns. Our results suggest that immunoglobulin could be used as a salvage therapy as an alternative to convalescent plasma but highly stringent patient selection is required due to the worldwide shortage of IVIg.